2008
DOI: 10.1017/s1368980007000481
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection among Egyptian children: impact of social background and effect on growth

Abstract: Objective: The study aim was to assess the prevalence of Helicobacter pylori infection in Egyptian schoolchildren and its effect on growth parameters. Design: A cross-sectional population-based study was conducted among 286 schoolchildren (168 boys and 118 girls), with a mean age of 11.04 6 0.19 years, to determine the prevalence of H. pylori. The presence of the bacterium was assessed using the [ 13 C]urea breath test. Relevant personal and socio-economic data on risk factors for infection were collected. Hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 36 publications
6
67
7
1
Order By: Relevance
“…Similar result was observed in some developing countries, in Africa (e.g. South Africa: 87% [16], Egypt: 72% [17]), in Latin America (e.g. Bolivia: 78% [18]) and in some Asian countries (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…Similar result was observed in some developing countries, in Africa (e.g. South Africa: 87% [16], Egypt: 72% [17]), in Latin America (e.g. Bolivia: 78% [18]) and in some Asian countries (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…The present study showed that there was no significant difference in the prevalence of infection between boys and girls regarding total antibodies or infection with virulent strain of H. pylori (anti Cag A Ig G positive) in the diabetics. This result comes in agreement with Mahmoud et al [10], who revealed that no gender difference in H. pylori infection was found. On the other hand, another study confirmed the male predominance of H. pylori infection [11], while the study of Kanbay et al [12] stated that H. pylori infected females were predominant as compared to males.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on Egyptian children with age ranging from 6 months to school age reported that H. pylori prevalence ranged from 15-75.38% (Bassily et al, 1999;Naficy et al, 2000;Mohammad et al, 2007). In most cases this was lower than findings of this study.…”
Section: Discussioncontrasting
confidence: 81%